2014
DOI: 10.4028/www.scientific.net/amm.556-562.4457
|View full text |Cite
|
Sign up to set email alerts
|

Research on Starting Pressure Gradient of Low Permeability Reservoir

Abstract: Due to the presence of starting pressure of low permeability reservoir, so researching on starting pressure gradient of low permeability reservoir is necessary. while starting pressure gradient is relevant to permeability and porosity, it can be obtained through laboratory experiments¡¢well testing interpretation method¡¢theory derivation combined with practical application method . The result of a large number of laboratory experiments shows: starting pressure is related to permeability .The greater the perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The simulation findings suggest that a high pressure gradient can mitigate the impact of the rough surface on CO 2 displacement in nanoporous media. Nonetheless, the practical pressure gradients in field (0.1−10 MPa/m) 43 are orders of magnitude lower than the pressure gradient employed in our simulation (10 5 MPa/m). As a result, theoretical predictions of CO 2 displacement efficiency in shale can significantly overestimate actual CO 2 displacement efficiency by only considering nanometer pore sizes of shale but without taking the rough surface into account.…”
Section: Co 2 Displacingmentioning
confidence: 67%
See 2 more Smart Citations
“…The simulation findings suggest that a high pressure gradient can mitigate the impact of the rough surface on CO 2 displacement in nanoporous media. Nonetheless, the practical pressure gradients in field (0.1−10 MPa/m) 43 are orders of magnitude lower than the pressure gradient employed in our simulation (10 5 MPa/m). As a result, theoretical predictions of CO 2 displacement efficiency in shale can significantly overestimate actual CO 2 displacement efficiency by only considering nanometer pore sizes of shale but without taking the rough surface into account.…”
Section: Co 2 Displacingmentioning
confidence: 67%
“…As the displacement pressure increases, the breakthrough time decreases, and the displacement ratio increases, which is similar to gaseous CO 2 displacement. Overall, it is important to consider the rough surface of nanoporous media in shale when estimating the displacement efficiency of supercritical CO 2 at practical pressure gradients (0.1–10 MPa/m) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from the TPG in tight oil reservoirs caused by ultralow permeability, the TPG in heavy-oil reservoirs is mainly attributed to the abnormal viscosity [11][12][13]. A large number of mechanism studies have shown that the TPG described in heavy-oil simulation could be summarized into the following three methods: pseudo threshold pressure gradient (PTPG) model, piecewise nonlinear model, and variable permeability model.…”
Section: Introductionmentioning
confidence: 99%